2009
DOI: 10.1016/j.ceb.2009.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral ER structure and function

Abstract: SummaryThe endoplasmic reticulum (ER) is a single continuous membrane-enclosed organelle made up of functionally and structurally distinct domains. The ER domains include the nuclear envelope (NE) and the peripheral ER, which is a network of tubules and sheets spread throughout the cytoplasm. The structural organization of the ER is related to its many different cellular functions. Here we will discuss how the various functional domains of the peripheral ER are organized into structurally distinct domains that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
133
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(137 citation statements)
references
References 44 publications
3
133
0
1
Order By: Relevance
“…3B, bottom panel). The purpose of the constant reorganization of the tubular ER network is not known; however, it is reasonable to suggest that ER dynamics could be required for the necessary functions of the ER, such as facilitating organelle contact for exchange of proteins, lipids, and Ca 2þ (Baumann and Walz 2001;English et al 2009). To further understand the nature of ER dynamics it is important to identify the unknown factors involved, including the factors linking ER tubules to the motor proteins on MTs during sliding dynamics.…”
Section: Er Dynamics and Assemblymentioning
confidence: 99%
“…3B, bottom panel). The purpose of the constant reorganization of the tubular ER network is not known; however, it is reasonable to suggest that ER dynamics could be required for the necessary functions of the ER, such as facilitating organelle contact for exchange of proteins, lipids, and Ca 2þ (Baumann and Walz 2001;English et al 2009). To further understand the nature of ER dynamics it is important to identify the unknown factors involved, including the factors linking ER tubules to the motor proteins on MTs during sliding dynamics.…”
Section: Er Dynamics and Assemblymentioning
confidence: 99%
“…From what we have learned so far, it is safe to say that the ER and the Golgi are multitasking organelles acting not only in series, but also collaborate to enable novel mechanisms that require temporal and spatial separation such as that observed with ERp44 and possibly, ER mannosidase I. Other membrane interfaces such as the GERL in which ER cisternae interdigitates with the trans-most Golgi cisternae or associate with the phospholipid surface of mitochondria or lipid droplets are likely to provide interesting twists on mechanisms previously ascribed to either organelles (Novikoff and Yam 1978;Halter et al 2007;English et al 2009;Lynes et al 2012). To underscore this notion, a subset of ER resident proteins have emerged as constituents of maturing phagosomes giving rise to a mechanistic basis for antigen cross presentation in innate immunity (Gagnon et al 2002;Houde et al 2003;Cebrian et al 2011;Campbell-Valois et al 2012).…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
“…To underscore this notion, a subset of ER resident proteins have emerged as constituents of maturing phagosomes giving rise to a mechanistic basis for antigen cross presentation in innate immunity (Gagnon et al 2002;Houde et al 2003;Cebrian et al 2011;Campbell-Valois et al 2012). The ER also generates peroxisomes (Titorenko et al 1997;Titorenko and Rachubinski 1998;van der Zand et al 2012), and a further specialized subset of ER is found beneath the cell membrane of many cells (English et al 2009). The Golgi apparatus, on the other hand, contributes part of its machinery to lipid droplet biogenesis, revealing a mechanistic link previously thought to be exclusive to that of the ER.…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
“…G. Voeltz (Boulder, CO, USA) has characterized the functionally and structurally distinct subdomains of the continuous ER membrane system, and is identifying the ER proteins that have roles in controlling ER shape (English et al, 2009). Recent discoveries indicate that reticulon and DP1/Yop1 shape the tubular ER.…”
Section: Er Structure and Interactomementioning
confidence: 99%